The economic development of continental Europe , 1780-1870 - Milward, Alan S.; Saul, S. B. (London : George Allen & Unwin, 1979)
This second edition of "The economic development of continental Europe, 1780-1870" is more than merely a textbook: it is an interpretative synthesis of a wide range of research on the subject in many countries. It is a work of fundamental interest to economists in which theories and hypotheses of economic development are examined in a much wider historical context. The edition has been revised and corrected throughout. Of particular value to students will be the revised and expanded sections on further reading, which are here brought up to date through the seven years since the book was first published.
Includes bibliographical references and index.
aia 15/11/2017
Loans
Keywords: Europe Economic-- Conditions; Economic History; Europe